(307) New Trends in Polytechnic Education with Special Reference to Planning of Manpower Demand in the Long Run (experience of G.D.R) الاتجاهات الجديدة في التعليم الفنى مع إشارة خاصة إلى تخطيط الطلب على القوى العاملة على المدى الطويل (تجربة جمهورية ألمانيا الديمقراطية) - Engert, M. (INP, 2024)
New Trends in Polytechnical Education with Special Reference to Planning of Manpower Demand in the Lon Run (experience of G.D.R)